Information Technologies in the Strategy for Tourist Destination Development in the Western Ukrainian Border Regions - Kyfiak, Vasyl; Кифяк, Олександр; Koroliuk, Yuriy (Studia Regionalne i Lokalne, 2023)
The article examines the peculiarities of the formation and development of tourist destinations in the western Ukrainian border regions. GMDH analysis of statistical indicators of tourism in Lviv, Ivano-Frankivsk, Zakarpattya, Volyn and Chernivtsi regions revealed the importance of information campaigns promoting local destinations. The strategy for tourist destination formation, information support and promotion in the western Ukrainian border regions is developed and the components of its realisation are described.
Keywords: information technologies, tourism, destinations, region, development strategy